Synthesis of modified K0.5Na0.5NbO3powder by molten-salt technique - Thanatep Phatungthane (2018)
© 2017 Trans Tech Publications. In the present work, the molten-salt method was applied to synthesize 0.948K0.5Na0.5NbO3-0.052LiSbO3powder. The powder properties after processing were investigated. Based on X-ray diffraction technique, pure perovskite phase was observed at a calcination temperature of 700°C which is lower than that required by the conventional solid-state reaction technique for ∼200°C. The XRD analysis showed that the powder had an orthorhombic symmetry which consistent with the Raman spectroscopy results. The powder exhibited very fine grain with narrow size distribution. Particle size of the obtained powders increased with increasing calcination temperature. Therefore, the molten-salt method is a simple and effective method to synthesize 0.948K0.5Na0.5NbO3- 0.052LiSbO3powder.